Ars moriendi a skandal śmierci.Rozważania nad "Ravelsteinem" Saula Bellowa - Jankowska, Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
This article deals with the modern cultural perception of the phenomenon of death. It attempts to describe the role that death plays in individual and social existencein the post-secular age. ‘Based on a critical reading of Saul Bellow’s novel Ravelstein the author analyzes the process of tabooization of death. Putting death under taboo is based on a new cultural paradigm which is connected with a new axiology where the highest values are the following: youth, vitality, strength, health and beauty. Death (which, obviously, is in contradiction to those values) appears as something ugly, cruel and shameful, and as something to be hidden from the public view. As death has been denaturalized and medicalized, it is no longer seen as something natural or as a kind of rite of passage. Without the religious context, death (understood as a kind of new taboo) becomes an individual and social trauma. Therefore, one looks for a “third path” and tries to place death between full acceptance and total rejection. Bellow’s character, Ravelstein, also looks for that “third path”.